A cooperação da Universidade Federal de São Carlos com a Sociedade - Oliveira, Rodrigo Maia de (2002)
The current context of the world economy heading for the globalization of markets leads to new approaches of the discussion on the role of the university as an essential agent to the progress of Science and Technology. The discussions have been pointing to the latent potential in the relationship between universities and industries as responsible, in great part, for the technological development of several knowledge areas on behalf of the society and, recently, the public universities are implementing actions that draw more attention to its social role. The objective of this study is to contribute for a better understanding of the matter involving the relationship between the university and the industry in Brazil, through a research accomplished in the Federal University of São Carlos (UFSCar). The choice of this university is justified by the important role that it has been carrying out in the regional context, consolidating, together with the University of São Paulo campus São Carlos, the local Pole of High Technology. Taking as study object the universe of 700 contracts managed by the Foundation of Institutional Support to the Scientific and Technological Development (FAI-UFSCar), it was possible to trace a prospect of the cooperation of UFSCar with its external partners for the period 1992-2000.